Outbreak investigation of acute diarrhoeal disease in a village of Dibrugarh District, Assam - Thaosen, Chandana; Kotoky, Manas J; Mahanta, Tulika G (Indian Journal of Community Health, 2024)
Lack of water sanitation and hygiene facilities (WASH) and practices are such that over 700 children under 5 years of age die every day of diarrhoeal diseases.(1) In recent past, despite substantial gains in access to WASH services almost 2.3 billion people worldwide still lack these basic human necessities.(2) Safe drinking water and basic sanitation are crucial interventions in fight against diarrhoeal mortality (WHO). Worldwide, each year, low sustainability in WASH services contributes to nearly two million deaths and 82 million disability-adjusted life years (DALYs) lost, which are preventable.(3)